Veronica Mars [videorecording (DVD)] - Thomas, Rob
On the eve of graduating law school, Veronica Mars has put Neptune and her amateur sleuthing days behind her. While interviewing at high-end New York law firms, Veronica Mars gets a call from her ex-boyfriend Logan who has been accused of murder. Veronica heads back to Neptune just to help Logan find an attorney, but when things don't seem right with how Logan's case is perceived and handled, Veronica finds herself being pulled back into a life she thought she had left behind.